Human aging and CD31(+) T-cell number, migration, apoptotic susceptibility, and telomere length - Kushner, Erich J. (American Physiological Society, 2010)
CD31(+) T cells, or so-called “angiogenic T cells,” have been shown to demonstrate vasculoprotective and neovasculogenic qualities. The influence of age on CD31(+) T-cell number and function is unclear. We tested the hypothesis that circulating CD31(+) T-cell number and migratory capacity are reduced, apoptotic susceptibility is heightened, and telomere length is shortened with advancing age in adult humans. Thirty-six healthy, sedentary men were studied: 12 young (25 ± 1 yr), 12 middle aged (46 ± 1 yr), and 12 older (64 ± 2 yr). CD31(+) T cells were isolated from peripheral blood samples by magnetic-activated cell sorting. The number of circulating CD31(+) T cells (fluorescence-activated cell sorting analysis) was lower (P < 0.01) in older (24% of CD3(+) cells) compared with middle-aged (38% of CD3(+) cells) and young (40% of CD3(+) cells) men. Migration (Boyden chamber) to both VEGF and stromal cell-derived factor-1α was markedly blunted (P < 0.05) in cells harvested from middle-aged [306.1 ± 45 and 305.6 ± 46 arbitrary units (AU), respectively] and older (231 ± 65 and 235 ± 62 AU, respectively) compared with young (525 ± 60 and 570 ± 62 AU, respectively) men. CD31(+) T cells from middle-aged and older men demonstrated greater apoptotic susceptibility, as staurosporine-stimulated intracellular caspase-3 activation was ∼40% higher (P < 0.05) than young. There was a progressive age-related decline in CD31(+) T-cell telomere length (young: 10,706 ± 220 bp; middle-aged: 10,179 ± 251 bp; and older: 9,324 ± 192 bp). Numerical and functional impairments in this unique T-cell subpopulation may contribute to diminished angiogenic potential and greater cardiovascular risk with advancing age.